Function of Latent TGFβ Binding Protein 4 and Fibulin 5 in Elastogenesis and Lung Development. Issue 1 (January 2015) - Dabovic, Branka; Robertson, Ian B.; Zilberberg, Lior; Vassallo, Melinda; Davis, Elaine C.; Rifkin, Daniel B.
<x xml:space="preserve">Abstract</x> Mice deficient in Latent TGFβ Binding Protein 4 (Ltbp4) display a defect in lung septation and elastogenesis. The lung septation defect is normalized by genetically decreasing TGFβ2 levels. However, the elastic fiber assembly is not improved in Tgfb2‐/‐;Ltbp4S‐/‐ compared to Ltbp4S‐/‐ lungs. We found that decreased levels of TGFβ1 or TGFβ3 did not improve lung septation indicating that the TGFβ isoform elevated in Ltbp4S‐/‐ lungs is TGFβ2. Expression of a form of Ltbp4 that could not bind latent TGFβ did not affect lung phenotype indicating that normal lung development does not require the formation of LTBP4‐latent TGFβ complexes. Therefore, the change in TGFβ‐level in the lungs is not directly related to Ltbp4 deficiency but probably is a consequence of changes in the extracellular matrix. Interestingly, combination of the Ltbp4S‐/‐ mutation with a fibulin‐5 null mutant in Fbln5‐/‐;Ltbp4S‐/‐ mice improves the lung septation compared to Ltbp4S‐/‐ lungs. Large globular elastin aggregates characteristic for Ltbp4S‐/‐ lungs do not form in Fbln5‐/‐;Ltbp4S‐/‐ lungs and EM studies showed that elastic fibers in Fbln5‐/‐;Ltbp4S‐/‐ lungs resemble those found in Fbln5‐/‐ mice. These results are consistent with a role for TGFβ2 in lung septation and for Ltbp4 in regulating fibulin‐5 dependent elastic fiber assembly. J. Cell. Physiol. 229: 226–236, 2014. © 2014 Wiley Periodicals, Inc.